DETERMINATION OF THE FOCAL MECHANISM OF EARTHQUAKE IN ALBERTA, CANADA (Φ = 58.16°N, Λ = -115.25°E, MW = 3.98) - Malytskyy, D.; Hrytsai, O.; Obidina, O.; Pavlova, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The aim of this paper is to determine focal mechanism of earthquake occurred in Alberta (Canada) province by using graphic method and to clarify the focus depth by doing correlation analysis of real and artificial seismograms. The graphic method is proposed for for determining the focal mechanism of earthquake in the region with low seismic activity. This method is based on P-waves polarity distribution into zones of compression and extension, and division of nodal planes. Fuzzy P-waves arrivals in the station and the value of the ratio of the S-wave amplitude to Pwave are important parameters. They define the relative location to the nodal plane. To use the graphical method the correct velocity model of the medium and clear records of the stations might be used. The results of construction of focal mechanism in Alberta (Canada) as the the region with low seismic activity are discussed. The focal mechanisms were constructed by graphic method with using the complete records from the station and documents about these records for the different depth of the source occurence. The comparative analysis of real and artificial seismograms is made. It is determined that seismic event occurred at a depth of 6 km.  For the first time the focal mechanism of the earthquake in Alberta is determined. The depth of the earthquake occurrence is specified by correlation analysis between the actual and artificial tracks (seismogram). The highest correlation coefficient is observed between real records and artificial seismograms calculated for the earthquake depth of 6 km, which indicates the depth of the earthquake source determined in this work. The results of this paper will be used for further study of Carpathian region seismicity, determination of the focal mechanisms of earthquake and analysis of stress-strain state of rocks in this region.
Keywords: focal mechanism; correlation analysis; nodal plane; the depth of earthquake source